STATISTICAL STUDY OF LABOR MOVEMENT IN NEW UZBEKISTAN - Akbarova Zaripa (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This study statistically analyzed the processes of labor mobility (employment, unemployment, migration, and inter-sectoral transition) in the conditions of New Uzbekistan. For the analysis, descriptive statistics, regression analysis, and index methods were used based on official macrostatistical data and sample observations. The results showed that the labor market is in a structural transformation stage, the share of the service sector is increasing, and there are significant differences across regions.